Review: Parkinson's disease: from synaptic loss to connectome dysfunction. (February 2016) - Bellucci, Arianna; Mercuri, Nicola Biagio; Venneri, Annalena; Faustini, Gaia; Longhena, Francesca; Pizzi, Marina; Missale, Cristina; Spano, PierFranco
Abstract: Parkinson's disease (PD) is a common neurodegenerative disorder with prominent loss of nigro‐striatal dopaminergic neurons. The resultant dopamine (DA) deficiency underlies the onset of typical motor symptoms (MS). Nonetheless, individuals affected by PD usually show a plethora of nonmotor symptoms (NMS), part of which may precede the onset of motor signs. Besides DA neuron degeneration, a key neuropathological alteration in the PD brain is Lewy pathology. This is characterized by abnormal intraneuronal (Lewy bodies) and intraneuritic (Lewy neurites) deposits of fibrillary aggregates mainly composed of α ‐synuclein. Lewy pathology has been hypothesized to progress in a stereotypical pattern over the course of PD and α ‐synuclein mutations and multiplications have been found to cause monogenic forms of the disease, thus raising the question as to whether this protein is pathogenic in this disorder. Findings showing that the majority of α ‐synuclein aggregates in PD are located at presynapses and this underlies the onset of synaptic and axonal degeneration, coupled to the fact that functional connectivity changes correlate with disease progression, strengthen this idea. Indeed, by altering the proper action of key molecules involved in the control of neurotransmitter release and re‐cycling as well as synaptic and structural plasticity, α ‐synuclein deposition may crucially impair axonal trafficking, resulting in a series of noxious events, whose pressure may inevitably degenerate into neuronal damage and death. Here, we provide a timely overview of the molecular features of synaptic loss in PD and disclose their possible translation into clinical symptoms through functional disconnection.